Axiological analysis of the construction and validation of an edumetric documentary instrument - Paucca Gonzales, Nelson (2020)
Abstract Educational research presents certain biases in what is referred to the construction of an edumetric documentary instrument and its validation process. This may be due to the lack of axiological awareness from some researchers, thesis experts, advisors and expert judges who have the moral obligation to validate the instrument through its items. To summarize what has been exposed previously the following objective is proposed; to notice the lack of ethics and morality of the people involved in the construction and validation process of an edumentric instrument. The analysis of the scientific article corresponds to the analytical - hermeneutical method in what is referred to the qualitative approach and the instrumental studies method in what is referred to the quantitative method. The hermeneutical method has allowed the strict analysis of the role of those who were mentioned before. The results discussion has established the differences between the construction of a psychometric and edumetric instrument, the second one is built due to the lack of previous studies and its validation follows the formulated theories in function to the variables and dimensions. Finally, it is concluded that the people involved in the edumetric construction lack axiological praxis.